Thoughts on the Nigerian economy : an industrialists perspective - Giwa, R. F. (Surulere, Lagos : Mednet, 1992)
A collection of contributions made by Chief Rufus Giwa at various occasions between 1989 and 1992 on the general theme of the economy and industry. It provides insight into the relationship between the nation's economic policies and the performance of the industrial sector.
Includes bibliographical references.
oif 26/07/16; rpm 31/08/16, ijb, 04/02/2019
Loans
Keywords: Economic conditions; Economic policy; Fiscal policy; Structural adjustment (Economic policy); Nigeria